A Participatory Comic Book Workshop to Improve Youth-Friendly Post-Rape Care in a Humanitarian Context in Uganda: A Case Study - Logie, Carmen H.; Okumu, Moses; Loutet, Miranda; Berry, Isha; McAlpine, Alyssa; Lukone, Simon Odong; Kisubi, Nelson; Mwima, Simon; Kyambadde, Peter (Global Health: Science and Practice, 2023)
Graphic medicine formats, such as comic books in which health information is presented alongside images, may be a useful learning tool to improve post-rape care and youth-friendly service provision among health care providers in humanitarian contexts. We describe the development and pilot-testing of a workshop using a comic book to improve youth-friendly post-rape care with providers in Bidi Bidi refugee settlement, Uganda. We conducted 6 focus groups with refugee young men (n=3) and women (n=3) aged 16-24 years and 28 in-depth individual interviews (refugee youth: n=12; health care providers: n=8; elders: n=8). Findings informed the development of a workshop that included a participatory comic book on sexual and gender-based violence (SGBV) and youth, SGBV stigma, youth-friendly health care, and post-exposure prophylaxis. Comic book illustrations specifically addressed health care confidentiality and examples of being a supportive health care provider. Then, we conducted a 1-day workshop with health care providers (n=20) that included structured activities addressing SGBV impacts and related stigma and included comic book discussions. Open-ended survey data were collected 8 weeks after the workshop to explore health care providers' experiences with the workshop, perceived impact of the intervention on their work, and support required to implement youth-friendly services for SGBV survivors. Qualitative data were analyzed using thematic approaches. Open-ended response data indicated that: comic book methods were informative and interactive; health care providers felt more empowered to offer youth-friendly services and spaces; and health care providers want additional SGBV training and institutional support for youth-friendly spaces and community engagement. A comic book intervention has the potential to meaningfully engage health care providers in humanitarian contexts to provide youth-friendly health care, acquire skills for engaging in SGBV prevention, create youth-friendly clinic spaces, and identify health care and community SGBV prevention needs.